The Application of Warm Steam Therapy Using Eucalyptus Oil Aromatherapy in Treating Respiratory Tract Infection in Children with Bronchopneumonia - Qur’aeni, Devi Nurul; Purbasari, Dwiyanti; Karlina, Nonok (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: Bronchopneumonia is an inflammation of the lung parenchyma caused by bacteria, viruses, fungi, or foreign objects. Simple inhalation therapy involves administering medication in the form of vapor into the respiratory tract using simple materials and methods. Method: This study is a case study with a qualitative descriptive approach, conducted in the Wijaya Kusuma Atas ward of Kardinah Tegal General Hospital. Data were obtained through nursing care assessment and documentation of patients with bronchopneumonia who were hospitalized and experienced airway clearance disorders. The intervention involved administering warm steam therapy using eucalyptus essential oil aromatherapy for 10–15 minutes over three days. Result: The case study results showed an improvement in airway clearance effectiveness in patients receiving eucalyptus essential oil steam therapy. Conclusion: Warm steam therapy using eucalyptus essential oil aromatherapy is effective as an additional intervention to address airway clearance issues in patients with bronchopneumonia.